(untitled) (Public Sector Economics - submission site, 2021)
In this paper we analyse expected liquidity driven changes in asset allocation of Croatian mandatory and voluntary pension funds based on long-term cash flow projections. For mandatory pension funds, expected long-term cash flow are simulated taking into account the life-cycle scheme, changes in the default fund for undecisive newcomers, expected returns of funds and certain demographic and economic assumptions. Analogously, cash flow simulations of voluntary pension funds are simulated, with an additional scenario of short-term outflows due to the possibility of withdrawing earlier. The growing need for liquidity of pension funds is expected to impact their asset allocations through the endeavour for more liquid portfolios even in a baseline scenario. In the case of more severe assumptions of various parameters of the model, the liquidity-driven reallocation is expected to influence long-term returns of pension funds that experience negative or low net inflows, and subsequently lead to negative liquidity premium.